Extended Adjuvant Endocrine Therapy in Breast Cancer: Evidence and Update — A Review. Issue 6 (2nd March 2017) - Jinih, Marcel; Relihan, Norma; Corrigan, Mark A.; O'Reilly, Seamus; Redmond, Henry P.
Abstract: The optimal duration and treatment strategies involving adjuvant endocrine therapy in early breast cancer remained largely undetermined. As data emerge on the various modalities of treatment in both pre‐ and postmenopausal groups, debates, and discussions continue. Most studies to date focused on the 5‐year duration of treatment consisting of mainly tamoxifen. The Arimidex, Tamoxifen, Alone or in Combination (ATAC) study demonstrated that anastrozole is superior to tamoxifen and has become the mainstream treatment in postmenopausal women with early breast cancer, although the duration was arbitrarily set for 5 years, analogous to tamoxifen treatment. Several clinical trials, however, have emerged to support extended endocrine therapy as it becomes clear that the recurrence risk of breast cancer does not decrease beyond the initial 5 years of treatment. The advent of molecular signatures also plays an important role in the breast cancer profiling, and where available should be incorporated in the overall decision‐making. Furthermore, side effects and noncompliance pose another issue in achieving an optimal treatment benefit. The decision‐making as regards to extended endocrine treatment should therefore focus not only on the cancer biology alone but also include treatment side effects, assessment of risk of recurrence and patients' preference. In this review, we present an overview of the published studies to date as well as ongoing studies on the topic to better refine the options for adjuvant hormonal therapy.